Assessment of black carbon radiative effects in climate models - Feichter, J; Stier, P (2012)
Black carbon (BC) from the burning of fossil fuel and biomass absorbs solar radiation and might intensify the greenhouse gas warming. Therefore, ideas to combat climate warming by reducing black carbon emissions emerged. However, black carbon emissions are generally accompanied by co-emission of other aerosols that predominantly scatter and have a cooling effect, so that the net forcing is substantially smaller, reducing mitigation potentials. Moreover, indirect effects on clouds are likely to exert additional cooling. As in situ measurements do not sufficiently sample the global atmosphere and satellite data does not provide the necessary detail on aerosol absorption, our only tools to estimate the effect of mitigation are numerical climate models. A review of current model estimates of black carbon radiative effects gives an average estimate of the direct radiative forcing as +0.33 W/m2, indirect effects of -0.11 W/m2 and through BC deposition on snow/ice surfaces of about +0.05 W/m2. A key limitation of these estimates is that the numerical models required for their global quantification are insufficiently constrained by observations. In addition, the comparison of instantaneous forcings generally overestimates the relative importance of black carbon and policy makers should consider alternative metrics, incorporating time-horizons. © 2012 John Wiley and Sons, Inc..